2018
DOI: 10.12659/msm.907277
|View full text |Cite
|
Sign up to set email alerts
|

Rho Kinase Type 1 (ROCK1) Promotes Lipopolysaccharide-induced Inflammation in Corneal Epithelial Cells by Activating Toll-Like Receptor 4 (TLR4)-Mediated Signaling

Abstract: BackgroundRho kinases (ROCKs) are the typical downstream effectors of RhoA, which can regulate corneal epithelial wound healing. In this study, the role of ROCK1 in lipopolysaccharide (LPS)-induced cornea inflammation was investigated.Material/MethodsThe expression of ROCK1 in human corneal epithelial cells (HCECs) was bilaterally modulated with ROCK1 expression vector and ROCK1 inhibitor Y-27632. The effects of ROCK1 modulation on the inflammatory response, cell viability, cell apoptosis, and cell cycle distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Previous studies suggested that nuclear factor-κB (NF-κB) signaling is an important pathway for the development of gastric cancer and ROCK1 is a key mediator of this spathway. [29][30][31][32] Hence, we hypothesized that NF-κB signaling might be involved in the regulatory mechanism addressed by circNRIP1/miR-182/ROCK1 axis in gastric cancer, which is needed to be explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that nuclear factor-κB (NF-κB) signaling is an important pathway for the development of gastric cancer and ROCK1 is a key mediator of this spathway. [29][30][31][32] Hence, we hypothesized that NF-κB signaling might be involved in the regulatory mechanism addressed by circNRIP1/miR-182/ROCK1 axis in gastric cancer, which is needed to be explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…11,48,49 Past studies have reported a correlation between TNF-α and ROCK; TNF-α induced activated Rho, whereas ROCK promoted translocation of NF-κB to the nucleus to accelerate the production of TNF-α. 50,51 Based on these results, we speculated that higher expression of TNF-α induced CMV-infected hCECs and active RhoA, resulting in translocation of NF-κB to the nucleus to induce apoptosis. Also, NF-κB translocation to the nucleus may accelerate the production of TNF-α to maintain RhoA in an activated state.…”
Section: Discussionmentioning
confidence: 96%
“…In corneal endothelial cells, it has been reported that overexpression of ROCK1 may trigger lipopolysaccharide-induced production of TNF-α and its downstream apoptosis, which could be attenuated with ROCK inhibitors. 51 Yang et al 50 reported a preservative effect of ROCK inhibitors on the apoptosis of microvascular endothelial cells via inhibition of the nuclear translocation of NF-κB and consequent suppression of the generation of TNF-α. We therefore hypothesize that ROCK inhibitors may modulate the CMV-infection-induced generation of TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is well established the role of cysteine in alleviating intestinal inflammation and oxidative stress through the inhibition the NF-κB and the activation of the Nrf2 signaling pathways [36], which modulates the proliferation of epithelial cell. Similarly, it is well known that the activation of NF-kB pathway is involved in corneal inflammation [37], which could justify the beneficial effects of l-cysteine on corneal regeneration.…”
Section: Discussionmentioning
confidence: 97%